97. Event related potentials recorded by intracerebral electrodes. Issue 4 (April 2016) - Pro, S.; Specchio, N.; De Palma, L.; Marras, C.E.; Fusco, L.; Vigevano, F.; Valeriani, M.
Abstract : Preoperative evaluation, by means of intracerebral electrodes, provides an opportunity to explore neural generators of ERPs and also N140 (a long latency SEP that is modulated by attention manipulations). We studied 5 pediatric patients with drug resistant epilepsy. ERPs and SEPs (to median and tibial nerve stimulation) were recorded from the intracerebral electrode contacts referred to the earlobe ipsilateral to the stimulation. The analysis was addressed to the electrode contacts where an inversion of neurophysiological component polarity was observed, or where the EP amplitude was higher. P300 was recorded by electrodes located in hippocampus; MMN was also well recorded by electrodes placed in opercular-insular cortex; N140, increased in amplitude during attention condition, showed the maximum amplitude in the frontal electrode contacts and in the opercular-insular traces. Numerous investigations revealed that generators of ERPS are independent and with a cortical-subcortical distribution too. In this short case series, we could show some brain areas clearly involved in the generation of P300, MMN and N140 components.